Cardiorespiratory parameters and glycated hemoglobin of patients with type 2 diabetes after a rehabilitation program. Issue 8 (February 2018) - Marques, Natália da Silva Freitas; Abreu, Luiz Carlos de; Santos, Bárbara Vieira dos; Neto, Cândido Ferreira Rodrigues; Silva, José Rener Cordeiro da; Braga, Karine Ketlem de Souza; Uchôa, Kariny da Silva; Moraes, Laila Maria Silva; Ferreira, Leillane Cristina de Paiva; Ribeiro, Natanael Guimaraes; Santos, Savio Lima dos; Silva, Tayná Almeida da; et al.
Abstract: Introduction: Cardiovascular autonomic dysfunction reflex of the pathophysiology of diabetes mellitus (DM) favors an increase in morbidity and mortality related to cardiovascular events, and for this reason has been one of the most studied clinical entities. Method: An experimental study of a randomized clinical trial type was therefore proposed to analyze the hemodynamic and glycemic response after the practice of a rehabilitation program in patients with type 2 diabetes mellitus (T2DM). In this clinical trial the patients will initially be submitted to an evaluation protocol that consists of assessing blood pressure, heart rate, Borg scale, respiratory rate, oxygen saturation, distance traveled through the 6-minute walk test, quality of life questionnaire, Pittsburgh sleep quality questionnaire, and still glycated hemoglobin and heart rate variability through the cardiofrequency meter. After careful evaluation of the patients, they will be submitted to a metabolic rehabilitation program composed of aerobic and resisted exercises, performed for 12 weeks, in 3 weekly meetings of 60 minutes each. With such evaluations, it will be possible to construct with evidence that it is possible to work safer metabolic rehabilitation programs in patients with T2DM or other diseases that generate cardiovascular risks, guaranteeing them an improvement in cardiorespiratory fitness, hemodynamic and glycemic variables, allowing improvement of the quality of life. Ethics and Dissemination: The protocol is approved by the host institution's ethics committee under the number 1.616.721. Results will be disseminated via peer-reviewed journal articles and conferences. This clinical trial is registered at ClinicalTrials.gov identifier: NCT3094767.